Pengaruh Sikap Kerja Kualitas Kehidupan Kerja Dan Motivasi Kerja Terhadap Kinerja Pegawai Sekretariat DPRD Kabupaten Padang Lawas - Abdollah Harahap; Suryadi Suryadi; Romi Fahriza; Iska Latifah (Manajemen dan Bisnis, 2022)
The problems of this research is how much influence   job attitude on employees performance. How much influence  quality work of life on employees performance. How much influence   job motivation  on employees performance. How much influence    job attitude, quality work of life and   job motivation  on employees performance. The purpose of this research is for know influence and analize of     quality job attitude on employees performance. For know influence and analize of  quality work of life on employees performance. For know influence and analize of   job motivation  on employees performance. For know influence  quality work of life,  job attitude and   job motivation  on employees performance. The sample in this research is 30 employees, with data analysis technique used is multiple linear regression analysis. The research result     job attitude effect positive and significanly on employees performance. Quality work of life effect positive and significanly on employees performance.   Job motivation  effect positive and significanly to employees performance.  Job attitude, quality work of life and   job motivation  effect positive and significanly to employees performance.